Complexin regulation of synaptic vesicle release: mechanisms in the central nervous system and specialized retinal ribbon synapses - Yun-Zhi Li; Yu Wang; Qing Jiao; Jing Chi; Yang Liang; Bin Fan; Guang-Yu Li (Cell Communication and Signaling)
Abstract Synaptic ribbons, recognized for their pivotal role in conveying sensory signals in the visual pathway, are intricate assemblages of presynaptic proteins. Complexin (CPX) regulates synaptic vesicle fusion and neurotransmitter release by modulating the assembly of the soluble NSF attachment protein receptor (SNARE) complex, ensuring precise signal transmission in the retina and the broader central nervous system (CNS). While CPX1 or CPX2 isoforms (CPX1/2) play crucial roles in classical CNS synapses, CPX3 or CPX4 isoforms (CPX3/4) specifically regulate retinal ribbon synapses. These isoforms are essential for sustaining synaptic plasticity related to light signaling, adapting to changes in circadian rhythms, and dynamically regulating visual function under varying light conditions. This review explores the regulation of synaptic vesicle release by CPX in both the CNS and retinal ribbon synapses, with a focus on the mechanisms governing CPX3/4 function in the retina. Additionally, by reviewing the role of CPX and ribbon synapse dysfunction in non-retinal diseases, we further hypothesize the potential mechanisms of CPX in retinal diseases and propose therapeutic strategies targeting CPX to address retinal and CNS disorders associated with synaptic dysfunction.